Effects of hexarelin (a ghrelin analogue) on fertilisation and the pre- and postnatal development of mice - Luque, Eugenia Mercedes (2010)
Ghrelin (Ghr) has been associated with reproductive physiology and pre- and postnatal development. The objectives of the present study were to evaluate the effects of hexarelin (HEX; 100 or 200 µg kg-1 day-1), a therapeutic Ghr analogue, on: (1) embryo development 60 h post ovulation, induced pharmacologically, in pregnant mice; (2) the physical, neurobiological and sexual development of offspring of female mice injected with HEX during the first, second or third week of pregnancy or throughout the entire pregnancy; and (3) adult memory acquisition in these offspring. We also evaluated the effects of chronic HEX administration on memory acquisition in adult mice. Treatment of non-pregnant female mice with HEX decreased ovulation rate. However, treatment of pregnant mice with HEX at any time during pregnancy tended to accelerate offspring maturation, regardless of bodyweight. This effect was only significant on neurobiological parameters following treatment during the first week. HEX treatment during the first week and/or throughout the entire pregnancy resulted in impaired memory acquisition in the offspring, with female mice being more susceptible to these effects. Similar results were observed for the effects of chronic HEX treatment on memory acquisition in adult mice. In conclusion, HEX seems to exert differential effects depending on when it is administered. Because HEX has started to be used therapeutically, its deleterious effects on ovulation and memory acquisition must be further evaluated.